Behead and live long or the tale of cathepsin L. Issue 2 (29th November 2017) - Streubel, Maria Karolin; Bischof, Johannes; Weiss, Richard; Duschl, Jutta; Liedl, Wolfgang; Wimmer, Herbert; Breitenbach, Michael; Weber, Manuela; Geltinger, Florian; Richter, Klaus; Rinnerthaler, Mark
Abstract: In recent decades Saccharomyces cerevisiae has proven to be one of the most valuable model organisms of aging research. Pathways such as autophagy or the effect of substances like resveratrol and spermidine that prolong the replicative as well as chronological lifespan of cells were described for the first time in S. cerevisiae . In this study we describe the establishment of an aging reporter that allows a reliable and relative quick screening of substances and genes that have an impact on the replicative lifespan. A cDNA library of the flatworm Dugesia tigrina that can be immortalized by beheading was screened using this aging reporter. Of all the flatworm genes, only one could be identified that significantly increased the replicative lifespan of S.cerevisiae . This gene is the cysteine protease cathepsin L that was sequenced for the first time in this study. We were able to show that this protease has the capability to degrade such proteins as the yeast Sup35 protein or the human α ‐synuclein protein in yeast cells that are both capable of forming cytosolic toxic aggregates. The degradation of these proteins by cathepsin L prevents the formation of these unfolded protein aggregates and this seems to be responsible for the increase in replicative lifespan.